Safe action in using pesticide among farmers: A scoping review - Manalu, Putranto; Hulu, Victor Trismanjaya; Samosir, Frans Judea; Buenita, Buenita; Hartono, Hartono; Siregar, Santy Deasy; Siagian, Masryna; Sihotang, Widya Yanti; Harahap, Emira Nadiah (Public Health of Indonesia, 2023)
Background: Pesticides can poison users if they do not follow pesticide use standards. This is because the active substances in these pesticide products can cause acute pain. Objective: The study aimed to identify the factors of safe behavior in using pesticides in farmers. Methods: This study employed a scoping review method. The literature search was carried out on the indexed databases of Google Scholar, Science Direct, Scopus, PubMed, Free Medical Journals, and ProQuest in English. There were 450 research articles, and 15 met the inclusion criteria. From the 15 journals, information was collected from the publication year 2015-2021, article titles, design, population, interventions, and results. Relevant study articles related to the topics were qualitatively analyzed using NVIVO-12 Plus. Results: The analysis showed that knowledge, safe behavior of using pesticides, farmers' education, and personal protective equipment are the dominant factors influencing the safe behavior of using pesticides on farmers. Conclusion: Farmers who do not comply with safe behavior will have a higher health risk because of the toxicity of pesticides that can be directly inhaled and enter through the pores of the farmers’ skin.